VIRTUAL SCREENING OF INDONESIAN HERBAL DATABASE TO FIND SIRTUIN 1 ACTIVATORS USING THE DOCKING METHOD - Aldisa, Olivia; Azminah; Erlina, Linda; Hayun; Yanuar, Arry (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Chemical compounds in plants often have benefits and efficacy that can be useful for medicine. Biochemistry and biomedicine research aims to develop new drugs for degenerative human diseases such as cancer, cardiovascular diseases, and diabetes mellitus. Humans have a protein that is the key for metabolic sensors in a variety of metabolic pathways, Sirtuin 1 (SIRT1). Currently, only resveratrol, fisetin, and quercetin, which are compounds from natural ingredients, have been tested as activators of SIRT1 even though there are many chemical compounds in plants that could potentially be SIRT1 activators. Four crystal forms act as SIRT1 activators: 4ZZH, 4ZZI, 4ZZJ, and 5BTR. Methods: In this study, we employed the docking of new molecular compounds from an Indonesian herbal database as SIRT1 activators. Virtual screening was done using AutoDock Vina. AutoDock Vina was validated beforehand to obtain the best grid box; based on this research, the best grid box for AutoDock Vina is 60 Ã— 60 Ã— 60. Results: The top 10 ranked compounds were obtained for each crystal form and for the same compounds of the four crystal forms, which are alpha-carotene, Cassiamin C, casuarinin, and lutein.